Factors Affecting Adoption of Educational Discipline and Satisfaction Level Among Higher Education Students - Irfan Raza (Journal of Education and Educational Development, 2020)
This study examines the education career change behavior of male and female students. Factors like current trends, own preferences, parental pressure, and career counselors can influence their career adoption. Quantitative method research design was conducted for the study and a sample of 268 students was taken: 145 female and 123 male students, from different public and private universities of Islamabad. Purposive sampling technique was applied for selection as respondents were those who had changed their career path during their educational life. The results showed that current and prevailing trends, one’s own decisions, and career counseling affect the choice and adoption of educational career, but parental influence does not influence education career change decision. Results are nearly similar for both genders, but male are more satisfied with education career change as compared to female respondents.
Keywords: Career adoption; career counseling; current trends; educational career; parental pressure; prevailing trends